Library automated loan services among Bachelor of Administrative Science and Policy Studies students in UiTM Kedah: a study on user satisfaction and ease of use / Che Noor Asma Che Kob - Che Kob, Che Noor Asma (2012)
Today's library services are experiencing a penod o f rapid change. The environment for information and knowledge sharing has been transformed by technology, services has been conver1 into automated services and have became the daffy tool for thousands of people, on both a personal and business level. These people no longer willing to spend their time for waiting and queued up for services that there were needed, but to go straight to the services and save their valuable time in the process. They also demand that the services were there whenever they needing it. Therefore, libraries throughout the wor1d have given their best efforts in order lo advance their services in order to fulfill the needs of the users In this case, the use of Information Technology or ICT has become the first measurement and as the medium to S{)lve these problems. From the use of Information Technology and Information Communication Technology in library services, has resulting into automated self-services In thlS r esearch scope which is automated self-check machine and book drop services The researcher will interpret o n users satisfaction and ease of use of automated loan services among the Administrative Science and Policy Studies students in UiTM Kedah Through this research, researcher will try to gain as much as information regarding the users satisfaction and ease of use toward using the automated loan services.